Gender Equality and the Independence of the Legal Profession Between Historical and Contemporary Perspectives (Italian Review of Legal History, 2024)
A reflection is proposed on gender equality in connection with the principle of independence of the legal profession, through a historical analysis from the liberal era, through fascism, and into the republican period up to the present day. On the one hand, the exclusion of women from the legal profession in the 19th century can be partly attributed to the limited autonomy of bar associations. On the other hand, their admission after 1919 did not bring about gender equality, with significant repercussions on the entire category.
Keywords: gender equality; ndependence of the legal profession; Italy; 19th-20th centuries